2007
DOI: 10.1038/sj.npp.1301603
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of α2-Adrenoceptors Suppresses Excitatory Synaptic Transmission in the Medial Prefrontal Cortex of Rat

Abstract: Stimulation of a 2 -, especially a 2A -adrenoceptor (AR), in the prefrontal cortex (PFC) produces a beneficial effect on cognitive functions such as working memory. a 2 -Adrenergic agonists like clonidine and guanfacine have been used experimentally and clinically for treatment of psychiatric disorders such as attention-deficit/hyperactivity disorder (ADHD) and schizophrenia. However, the neurophysiological actions of a 2 -ARs in the PFC are poorly understood. In the present study, we recorded field excitatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 52 publications
2
50
0
Order By: Relevance
“…Our work suggested that under normal physiological conditions, the α 2A -adrenoceptors in pyramidal cells can be activated through Gi-cAMP-HCN signaling [78] . On the other hand, 230 under stress, activation of α 2A -adrenoceptors to protect PFC functions might occur via the Gi-cAMP-PKA-CaMKII-AMPAR signaling pathway [76] .…”
Section: Adhd Phenotypesmentioning
confidence: 72%
“…Our work suggested that under normal physiological conditions, the α 2A -adrenoceptors in pyramidal cells can be activated through Gi-cAMP-HCN signaling [78] . On the other hand, 230 under stress, activation of α 2A -adrenoceptors to protect PFC functions might occur via the Gi-cAMP-PKA-CaMKII-AMPAR signaling pathway [76] .…”
Section: Adhd Phenotypesmentioning
confidence: 72%
“…Formal proof that a 2 -adrenoceptor antagonists evoke the release of glutamate release remains to be acquired (cf. Ji et al, 2008b).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, though drugs that target brain monoamine neurotransmitters are currently the mainstay of psychotropic medications, an emerging view is that the therapeutic effects of such medications may be underpinned by monoamineeglutamate interactions (see above citations). The points of interaction between monoamines and glutamate are likely to be many, and range from glutamatergic modulation of the activity of midbrain monoaminergic neurones (Tao and Auerbach, 2000) to cross-talk between postsynaptic monoaminergic and glutamate receptor-mediated signalling (Marek et al, 2000;Svenningsson et al, 2007;Gonzalez-Maeso et al, 2008) to monoamine receptor-mediated modulation of glutamate release in the cerebral cortex (Marcus et al, 2005;Millan, 2006;Ji et al, 2008aJi et al, , 2008b.…”
Section: Introductionmentioning
confidence: 98%
“…From this aspect, results of our experiments agree with findings of other authors who observed inhibitory effects of applications of clonidine on background discharges and responsiveness of neurons of the basolateral amygdalar nucleus [4,5], postsynaptic Footnote. ** P < 0.01; *** P < 0.001. currents in cells of the rat prefrontal cortex [6], and neuronal activity in the ventral anterior (VA) and ventral lateral (VL) nuclei of the thalamus [7]. The inhibitory influence of clonidine applied in mild doses can be related to the fact that moderate excitation of presynaptic α2 adrenoreceptors mimics the inhibitory effect of noradrenaline on neuronal networks in the FRA.…”
Section: Discussionmentioning
confidence: 99%